2022
DOI: 10.3389/fmicb.2022.755189
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Disturbs Gut Homeostasis and Reshapes Serum Metabolome, Inducing Neurotoxicity and Abnormal Behaviors in Mice

Abstract: As an illicit psychostimulant, repeated methamphetamine (MA) exposure results in addiction and causes severe neurotoxicity. Studies have revealed complex interactions among gut homeostasis, metabolism, and the central nervous system (CNS). To investigate the disturbance of gut homeostasis and metabolism in MA-induced neurotoxicity, 2 mg/kg MA or equal volume saline was intraperitoneally (i.p.) injected into C57BL/6 mice. Behavioral tests and western blotting were used to evaluate neurotoxicity. To determine al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 80 publications
2
14
0
Order By: Relevance
“…Recently, the metabolomic profiling in METH addicts and METH‐exposed animals were evaluated in several studies 11–14 . In the present study, we found that METH addicts had signs of malnutrition, as indicated by reduced levels of Tbil, Cr and BUN in the blood of METH addicts.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Recently, the metabolomic profiling in METH addicts and METH‐exposed animals were evaluated in several studies 11–14 . In the present study, we found that METH addicts had signs of malnutrition, as indicated by reduced levels of Tbil, Cr and BUN in the blood of METH addicts.…”
Section: Discussionsupporting
confidence: 56%
“…Recently, the metabolomic profiling in METH addicts and METHexposed animals were evaluated in several studies. [11][12][13][14] In the present study, we found that METH addicts had signs of malnutrition, as indicated by reduced levels of Tbil, Cr and BUN in the blood of METH addicts. Consistent with previous reports, 12 we found that METHaltered metabolites were mainly related to amino acid metabolism and energy metabolism.…”
Section: Sex-specific Alteration Of Serum Metabolitessupporting
confidence: 55%
See 1 more Smart Citation
“…MA-administered rats exhibited rapid and marked changes in energy metabolism, nervous system, and membrane lipid metabolism [33,34], inducing neurotoxicity and locomotor sensitization, depression-, and anxiety-like behaviors [35]. Human brain tissue and cerebrospinal uid are not readily available due to ethical and safety constraints [36].…”
Section: Introductionmentioning
confidence: 99%
“…Kemp used an exposure to early life stress model to investigate the relationship between altered gut microbiome and depression and cardiovascular disease, showing that the model reduced microbial alpha diversity and altered microbial composition ( Kemp et al, 2021 ). A recent study found that dysregulation of gut microbiome composition contributed to the development of depression-like behavior induced by chronic myocardial infarction, suggesting that exogenous modulation of gut microbiome composition may be a potentially important strategy for treating depression-like behavior caused by adverse cardiac events ( Zhang et al, 2022 ). Our previous study similarly showed that mainly Desulfovibrio and Akkermansia were altered within the gut microbiome of the AS co-depression mouse model compared to the Control group of mice and confirmed that some lipid metabolites in the brain are strongly associated with some bacteria ( Hu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%